Canon and criterion in Christian theology : from the Fathers to feminism - Abraham, William J. 1947- (Oxford University Press, 1998)
The book provides an original and important narrative on the significance of canon in the Christian tradition. Standard accounts of canon reduce canon to scripture and treat scripture as a criterion of truth. Scripture is then related in positive or negative ways to tradition, reason, andexperience. Such projects involve a misreading of the meaning and content of canon -- they locate the canonical heritage of the church within epistemology -- and Abraham charts the fatal consquences of this move, from the Fathers to modern feminist theology. In the process he shows that thecentral epistemological concerns of the Enlightenment have Christian origins and echoes. He also shows that the crucial developments of theology from the Reformation onwards involve extraordinary efforts to fix the foundations of faith. This trajectory is now exhausted theologically and spiritually. Hence, the door is opened for a recovery of the full canonical heritage of the early church and for fresh work on the epistemology of theology.